2009
DOI: 10.1038/nm.2026
|View full text |Cite
|
Sign up to set email alerts
|

The obesity susceptibility gene Cpe links FoxO1 signaling in hypothalamic pro-opiomelanocortin neurons with regulation of food intake

Abstract: Reduced food intake brings about an adaptive decrease in energy expenditure that contributes to the recidivism of obesity following weight loss. Insulin and leptin inhibit food intake through actions in the central nervous system that are partly mediated by FoxO1. We show that FoxO1 ablation in pro–opiomelanocortin (Pomc) neurons (Pomc–Foxo1−/−) reduces food intake without affecting energy expenditure. Analyses of hypothalamic neuropeptides in Pomc–Foxo1−/− mice reveal selective increases of α–Msh and COOH–cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(128 citation statements)
references
References 55 publications
2
125
1
Order By: Relevance
“…The present study supports the previous reports in which CNFoxO1 expressed in the hypothalamic ARC by stereotactic adenoviral delivery inhibited Pomc gene expression (13) and confirms that FoxO1 in POMC neurons regulates Pomc gene expression. During the revision of this manuscript, Plum et al (26) reported that FoxO1 ablation in POMC neurons increased ␣-melanocyte-stimulating hormone (␣-MSH) due to increased expression of carboxypeptidase E and decreased food intake. We could not exclude the possibility that FoxO1 affected ␣-MSH protein level directly.…”
Section: Discussionmentioning
confidence: 99%
“…The present study supports the previous reports in which CNFoxO1 expressed in the hypothalamic ARC by stereotactic adenoviral delivery inhibited Pomc gene expression (13) and confirms that FoxO1 in POMC neurons regulates Pomc gene expression. During the revision of this manuscript, Plum et al (26) reported that FoxO1 ablation in POMC neurons increased ␣-melanocyte-stimulating hormone (␣-MSH) due to increased expression of carboxypeptidase E and decreased food intake. We could not exclude the possibility that FoxO1 affected ␣-MSH protein level directly.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that defective processing of proinsulin or immature beta cells may be present in these patients and that rapamycin treatment could restore the correct function. It has also been shown that the transcription factor, forkhead box O1 (FOXO1), affects carboxypeptidase E processing of hormone in the hypothalamus and that the mechanistic target of rapamycin (mTOR) pathway affects this process [29]. It would, therefore, be interesting to determine the effects of rapamycin on FOXO1 translocation and carboxypeptidase levels in the beta cell.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, leptin and insulin promote pFOXO1 and prevent its translocation to the nucleus (Kim et al 2006). This results in increased expression of Pomc (Belgardt et al 2008, Ernst et al 2009, Plum et al 2009) and decreased expression of Agrp (Kitamura et al 2006). Quite opposite to leptin and insulin, we demonstrated that central ghrelin administration increased both hypothalamic FOXO1 and pFOXO1 to a similar extent.…”
Section: Ghs-r 1amentioning
confidence: 99%